How does student peer review influence perceptions, engagement and academic outcomes? A case study - Mulder, Raoul; Baik, Chi; Naylor, Ryan; Pearce, Jon (Assessment and evaluation in higher education, 2014)
Involving students in peer review has many pedagogical benefits, but few studies have explicitly investigated relationships between the content of peer reviews, student perceptions and assessment outcomes. We conducted a case study of peer review within a third-year undergraduate subject at a research-intensive Australian university, in which we examined: (1) students' perceptions of the peer review process before and after peer review, (2) content of the peer reviews and what kinds of feedback were adopted and (3) the effect of participation in peer review on performance (grades) in the assessment task. Students overwhelmingly perceived peer review to be beneficial, and the opportunity to participate in peer review resulted in a significant improvement in the quality of work submitted for assessment. Students who benefited most from peer review were those of below-median performance, and the magnitude of benefit was related to the degree to which students engaged with the peer review process. Our study confirms that participation in peer review can lead to important improvements in performance and learning outcomes.